2022
DOI: 10.1038/s41598-022-08117-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of quality of alcohol-based hand sanitizers used in Johannesburg area during the CoViD‐19 pandemic

Abstract: Since the outbreak of the Coronavirus Disease 2019 (CoViD-19), the World Health Organization has recommended that, in absence of soap and water, alcohol-based hand sanitizer can be used to prevent the transmission of coronaviruses. Unfortunately, many media and anecdotal reports indicate that many alcohol-based hand sanitizers sold in South Africa are substandard and some contain potentially toxic ingredients. The study aimed to identify hand sanitizers used in the Johannesburg area during the CoViD-19 pandemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 12 publications
(21 reference statements)
1
8
0
Order By: Relevance
“…However, local researchers found that 41% (37/94) of the alcohol-containing sanitizers contained less than 60% v / v alcohol. Ethyl acetate, isobutanol, and other non-recommended alcohols (methanol, 1-propanol, and 3-methyl-butanol) were detected [ 17 ]. Alcohol components are the major active ingredients in most ABHSs, where they disrupt the cell wall and or cell membranes by denaturing proteins and dissolving lipids [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, local researchers found that 41% (37/94) of the alcohol-containing sanitizers contained less than 60% v / v alcohol. Ethyl acetate, isobutanol, and other non-recommended alcohols (methanol, 1-propanol, and 3-methyl-butanol) were detected [ 17 ]. Alcohol components are the major active ingredients in most ABHSs, where they disrupt the cell wall and or cell membranes by denaturing proteins and dissolving lipids [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In South Africa, hand sanitizers are not well regulated, and the product’s or manufacturer’s claims of microbial effectiveness are not verified. Hence, ineffective products enter the market leading to a false sense of security, as highlighted by a recent study that evaluated the alcohol content of hand sanitizers [ 17 ]. Due to a paucity of information on microbial effectiveness, this study aimed to investigate the anti-bacterial effectiveness of hand sanitizers commonly used in healthcare and community settings in Johannesburg, South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Nairobi showed about 14.9% of the tested 74 samples had methanol, instead of ethanol, as the main component of ABHS [ 30 ]. Another study in Johannesburg area revealed that 3 of the 94 different hand sanitizer products were found to contain no alcohol [ 31 ]. Such circulation of falsified hand sanitizer products in the market compromises the control of infection transmission and may expose users to the undesired effects.…”
Section: Discussionmentioning
confidence: 99%
“…SSC) which indicates the need for close control of such companies by the regulatory body. Such quality defect of the hand sanitizers may lead to poor hand hygiene and contributing to healthcare-associated infections as the study samples were also meant for use in healthcare settings.A similar study done in Johannesburg resulted in 37 (41%) products containing less than 60% v/v alcohol [ 31 ]. Additional literature have also reported the circulation of substandard ABHS in various market places [ 31 , 37 – 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation